ALAT PEMBUAT PUPUK ORGANIK OTOMATIS BERBASIS ARDUINO UNO - Angraini, Amelya Devi; Latifah, Hilma; Sulistyo, Eko; Muharani, Laily (Politeknik Manufaktur Negeri Bangka Belitung, 2025)
An Arduino Uno-based Automatic Organic Fertilizer Making Tool has been developed to transform household organic waste into organic fertilizer automatically. The tool utilizes Arduino Uno technology, incorporating sensors like the pH sensor and DHT22 sensor to monitor acidity, temperature, and humidity levels during the fertilizer-making process. It systematically processes organic waste through automation, controlling composting parameters in real-time for optimal decomposition and high-quality fertilizer production. The user-friendly system includes a stirrer and humidity control mechanism, along with an LCD screen for monitoring compost conditions. By effectively integrating sensor technology, the tool enhances productivity in organic waste processing and offers a practical solution for converting household waste into beneficial products. This innovation supports environmental preservation and resource utilization efforts in the community.